Tracking errors and optical scatter in a solar tracker with linear regression error correction - Wood, Norman B., author; Cox, Stephen K., author (Colorado State University. Libraries, 1998)
Tracking errors were assessed for a computer controlled solar tracker. The effects of optical scattering on radiometric measurements performed with the tracker were also evaluated. As the position of the tracker is iteratively corrected over time, linear regression is used to calculate a best-fit correction for tracking error. The performance of the tracker was found to be sensitive to the timing of the iterative corrections and to the errors associated with those corrections. Using an optimized scheme for iterative corrections in a field test, the average tracking error was found to be 0.11 ± 0.05 degrees for 48 hours following the final iterative correction. The solar tracker may be fitted with a mirror which can reflect the image of a target into an instrument. Because the mirror is exposed to multiple sources of illumination (direct sunlight, skylight, and light from surrounding objects) the scattering properties of the mirror are important. The intensity of light scattered from the mirror was compared with the intensity of diffuse skylight. Scatter from the diffuse field incident on the mirror (background scatter) was found to be more significant than scatter from the direct solar beam, and both were significant compared to the intensity of diffuse skylight. Background scatter ranged from 20% to 70% of the total measured signal, depending on scattering geometry and wavelength. Solar scatter ranged from 1% to 20%, also depending on scattering geometry and wavelength. The scattering properties of the mirror, as measured by the bidirectional reflectance distribution function, appeared to be anisotropic, possibly because of surface defects. For the wavelengths examined, the scattering properties did not follow the wavelength scaling law predicted by Rayleigh-Rice theory for clean, smooth, front-surface reflectors.
March 1998.
Also issued as Norman Bryce Wood's thesis (M.S.) -- Colorado State University, 1998.
Keywords: Solar radiation -- Measurement; Solar activity -- Measurement